Pastoral Leadership and Congregational Engagement in Faith Growth: A Study of 1 Peter 5:2 - Antoni Simamora; Andreas Eko Nugroho; Kornellius Rulli Jonathans (Program Pascasarjana UKIM, 2025)
This study explores the relationship between pastoral leadership and congregational involvement in fostering faith growth based on 1 Peter 5:2, using GBIMiracle Service Cibubur (GBI MSC) as a case study. Employing a qualitative approach with a case study design, data were collected through in-depth interviews with church leaders and members, direct observation, and document analysis. Thematic and interpretative analyses were conducted to uncover the dynamics between leadership practices and congregational participation. Findings reveal that pastoral leaders play multifaceted roles, including those of spiritual guides, teachers of the Word, counselors, motivators, and caregivers. However, several challenges arise, including a limited number of committed ministry personnel, an imbalance between ministry and personal life, interpersonal conflicts, and insufficient communication with congregants. Congregational involvement, fostered through ministry opportunities that utilize talents, mentoring, spiritual formation, and community fellowship, significantly contributes to both individual and collective faith growth. Active participation enhances spiritual maturity, character transformation, and a deeper connection with God. This study concludes that effective pastoral leadership, rooted in biblical values and responsive to the needs of the congregation, is essential for sustainable faith development. Personal spiritual consistency, leadership capacity, supportive community structures, and congregational engagement all influence leadership effectiveness. The study offers practical insights and theological reflection for strengthening church leadership and participatory discipleship in contemporary local church contexts.